Metabolite identification of spontaneously fermented papaya leaf / Hasrina Azren Yunus - Yunus, Hasrina Azren (2018)
This study was conducted to identify the flavonoid component and phenolic acid in C. papaya fermented extract. C. papaya leaf typically has high amount of flavonoid compound such as, quercetin and kaempferol. Here, the metabolite components of the fermented C. papaya leaf extract was resolved using chromatograpic analysis i.e. UHPLC followed by identification specific compounds using online database. Based on the database analysis, the compound detected i.e. Kaempferide 7-Methylkaempferol and 3-O-Methylkaempferol is a group of flavonoids kaempferol while 6-Acetylphenazine-1-carboxylic acid is a phenolic acid compound that are known to have great anti-oxidant and anti-cancer activity. From the result obtained, it can be conclude that the extracted C. papaya fermented contains flavonoid and phenolic compounds.